2020
DOI: 10.4028/www.scientific.net/msf.992.952
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical Foundations and Practical Significance of Unification of Metallic and Nonmetallic Substances and Materials within a Unified Model of Chemical Bond

Abstract: In the present work, in the framework of solving the problem of obtaining a new generation of materials with a set of properties not inherent in traditional metal and non-metal types, the practical necessity of developing a unified approach to designing their structure and properties is substantiated. Within the framework of the paradigm of multi-level structural organization of materials, based on a single model of chemical bonding, a generalization of physicochemical prrinciples was carried out, revealing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…These data are in good agreement with the findings of previous studies [ 23 ] after 137 Cs was administered as a chloride into the body. However, Sirotkin [ 24 ] showed that transfer factor of 137 Cs of chicken meat for 30 days feeding was 2.4 times lower than with 390 days feeding. Astasheva [ 25 ] reported that biological half-life accumulation of adult geese muscles was 5 days, and for liver it was 1 day.…”
Section: Resultsmentioning
confidence: 99%
“…These data are in good agreement with the findings of previous studies [ 23 ] after 137 Cs was administered as a chloride into the body. However, Sirotkin [ 24 ] showed that transfer factor of 137 Cs of chicken meat for 30 days feeding was 2.4 times lower than with 390 days feeding. Astasheva [ 25 ] reported that biological half-life accumulation of adult geese muscles was 5 days, and for liver it was 1 day.…”
Section: Resultsmentioning
confidence: 99%
“…Since chemical energy is the main source of heat and electricity, the authors propose a new scientific foundation for the systematization and quantitative assessment of the energy characteristics of chemical compounds of elements (chemicals). It is based on a comprehensive assessment of the contribution of the composition of chemical compounds and their chemical bond type, based on a single model of chemical bond and the "System of chemical bonds and compounds" (SCBC) in the form of a "Chemical Triangle" (CT) [6][7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the use of this basic scientific innovation for the first time made a symbiosis of the approach of two outstanding Russian chemists: D. I. Mendeleev's periodic system of atoms (composition -property) and A. M. Butlerov's theory of chemical structure of matter (composition -chemical structure -property). As a result, this led the authors to create (Figure 3) a truly chemical system -the System of chemical bonds and compounds (SCBC) and a new paradigm for the systematic study of chemical substances (composition -chemical bond and structure -property) [6][7][8][9][10][11][12][13]. The foundation was laid for the creation of a database on the system digitalization and evaluation of the energy stored in various chemicals (gas, coal, fuel oil, peat, wood, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation